Letter - Henson, J.
027-0048-001 The Seafarers' Benefit Insurance Co., Limited. REGISTERED UNDER THE COMPANIES ACT. INSURANCE BROKERS. P.R. HENSON, Manager. Phone: Cardiff 5382 YOUR REF. OUR REF. Chief Office 2 STUART STREET, CARDIFF. 4th November 1939. H. V. Tewson Esq, Assistant Secretary, Trades Union Congress, LONDON. Dear friend Tewson, The bearer Senor Manuel Sasieta, is a personal friend of ours and a business man who now has the opportunity of proceeding to Tangier for an Irish Company whose letter he will show you. Difficulty has arisen on account of our government having cancelled these passports issued by the late Republican Government and it will be necessary for him to obtain a permit to proceed to Tangier. We should be obliged if you would assist him with the Home Office in obtaining the necessary permit. Best wishes, Yours sincerely, J.Henson 292/946/27/48